"We don't do that in Germany!" A critical race theory examination of Turkish heritage young adults' school experiences. (October 2019) - Moffitt, Ursula; Juang, Linda P; Syed, Moin
Turkish heritage students are underrepresented at university-track secondary schools in Germany, yet the institutional discrimination contributing to this ongoing disparity often remains unquestioned, situated within inequitable norms of belonging. Drawing on critical race theory and a risk and resilience framework, the current study investigated the interplay between institutional and interpersonal discrimination in relation to exclusionary norms enacted in university-track schools. Using thematic analysis, interviews with eight Turkish German young adults from multiple regions of Germany were analyzed, highlighting the need for culturally responsive teaching, more teacher reflexivity regarding bias, a greater focus on equity, and more direct discussions of racism and its impact.